Effects of short-term immersion and brushing with different denture cleansers on the roughness, hardness, and color of two types of acrylic resin - Panariello, Beatriz Helena Dias [UNESP]; Izumida, Fernanda Emiko [UNESP]; Moffa, Eduardo Buozi [UNESP]; Pavarina, Ana Claudia [UNESP]; Jorge, Janaina Habib [UNESP]; Giampaolo, Eunice Teresinha [UNESP] (My University, 2015)
Purpose: To investigate the cumulative effects of brushing (B) or immersion (I), using different cleansing agents, on the surface roughness, hardness and color stability of a heat-polymerized denture resin, Lucitone 550 (L), and a hard chairside rcline resin, Tokuyama Rebase Fast II (T). Methods: A total of 316 specimens (10x2 mm) were fabricated. The specimens (n= 9) were divided into brushing or immersion groups according to the following agents: dentifrice/distilled water (D), 1% sodium hypochlorite (NaOCI), Corega Tabs (Pb), 1% chlorhexidine gluconate (Chx), and 0.2% peracetic acid (Ac). Brushing and immersion were tested independently. Assays were performed after 1, 3, 21, 45 and 90 brushing cycles or immersion of 10 seconds each. Data were evaluated statistically by repeated measures ANOVA. Tukey's honestly significant difference (HSD) post-hoc test was used to determine differences between means (α= 0.05). Results: For L there was no statistically significant difference in roughness, except a significant decrease in roughness by brushing with D. T showed a significant effect on the roughness after 90 immersions with Ac. Hardness values decreased for L when specimens were immersed or brushed in NaOCI and Pb. The hardness of T decreased with increases in the repetitions (immersion or brushing), regardless of the cleaning method. Values of color stability for L resin showed significant color change after brushing with and immersion in Ac and Pb. Brushing with D exhibited a higher incidence of color change. For T there were no significant differences between cleaning agents and repetitions in immersion. A color change was noted after three brushings with the Ac, Chx, and D. Brushing with dentifrice decreased roughness of L. Immersion in or brushing with NaOCI and Pb decreased the hardness of L. For T, hardness decreased with increases in immersions or brushing. Color changes after the immersion in or brushing with cleaning agents were clinically acceptable according to National Bureau of Standards parameters for both resins.